Zinc (Zn) Accumulation in Mantis Shrimp (Harpiosquilla raphidea) from Sungsang, Banyuasin - Syekhan, Ryan; Putri, Wike Ayu Eka; Aryawati, Riris; Barus, Beta Susanto; Agustriani, Fitri; Melki, Melki (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Sungsang area in the Musi River estuary is an important fishing ground that is potentially exposed to zinc (Zn) contamination due to intensive anthropogenic activities. This study aimed to analyze Zn accumulation in mantis shrimp (Harpiosquilla raphidea) and to evaluate its consumption safety. Samples were collected from local collectors and analyzed using flame atomic absorption spectrophotometry in accordance with SNI 2354-13:2014. The results showed that Zn concentrations ranged from 20.24 to 21.27 mg/kg, with an average of 20.70 mg/kg, remaining below the maximum permissible limit established by Dirjen POM (1989). Risk assessment based on estimated intake indicated that Zn exposure from mantis shrimp consumption is within safe limits for humans. Overall, these findings confirm that mantis shrimp from Sungsang are safe for consumption with respect to Zn contamination. This study provides scientific evidence for food safety assessment and underscores the need for continuous monitoring of heavy metal contamination to support sustainable coastal resource management.